A presença social em ambientes virtuais de aprendizagem: análise de aspectos afetivos, interativos e coesivos na troca de mensagens eletrônicas - Gomes, Carolina Lacerda Motta de Oliveira (2013)
Due to the dissemination of new information and communication technologies, distance relationships are present in our everyday life, whether in a personal scope, a business scope, or even an academic scope. When we virtually relate with others using computer mediated communication, we are able to acknowledge the other self through the utilized media. This social presence can be assessed by verifying traces of its interactive, cohesive and affective aspects. This dissertation focus on verifying the way social presence and its affective, interactive and cohesive aspects are found in messages exchanged on a virtual learning environment. The study is justified by the possibility of widening the discussion on new information technology mediated communications, discussing issues related to administration, technology, sociology, psychology and education. To accomplish the intended results for this study, a content analysis was performed in the messages exchanged by teachers and students of undergraduate programs of an educational institution, using two different features available on a virtual learning environment. To foster this analysis the community of inquiry framework was adopted to retrieve the literature based indicators for the three aspects of social presence. As an outcome, the coded and classified exchanged messages were analyzed and it was possible to notice that there are significant differences achieved when different tools are used for the communication among teachers and students.